Association between exposure to polycyclic aromatic hydrocarbons and infections with human papillomavirus and herpes simplex virus type 2 - Shuping Yang; Yingjing Wu; Qi Ding; Tingting Hao; Ziyi Zhu; Yingying Wang; Yuee Huang; Yali Liang (Scientific Reports)
Abstract The study aimed to investigate the association between co-exposure to polycyclic aromatic hydrocarbons (PAHs) and infection with human papillomavirus (HPV) or herpes simplex virus type 2 (HSV-2) in a representative sample of the adult female population in the United States. A cross-sectional analysis was conducted using data from 4,284 participants in the National Health and Nutrition Examination Survey (NHANES). Logistic regression and stratified analyses were used to assess associations between individual PAH exposures and the prevalence of HPV and HSV-2 infection. Weighted quantile sum (WQS) regression was applied to explore the association between combined PAHs exposures and infection outcomes. After adjusting for covariates (age, race, poverty-to-income ratio, education, physical activity, smoking status, and creatinine), logistic regression identified positive associations between exposure to 2-NAP, 1-PHE, and 1-PYR and HPV infection, and between 1-NAP, 3-FLU, 2-FLU, 1-PHE, 1-PYR, 9-FLU, and 2&3-PHE and HSV-2 infection. Subgroup analyses suggested stronger associations among younger women (20–39 years) and never smokers. WQS regression indicated that co-exposure to PAHs was associated with increased odds of HPV infection (OR = 1.29, 95% CI: 1.06–1.57) and HSV-2 infection (OR = 1.81, 95% CI: 1.40–2.34), with naphthol contributing the highest weight to the mixture effect. In conclusion, PAHs exposure was associated with a higher prevalence of HPV and HSV-2 infections in this cross-sectional study. These findings provide epidemiological evidence of a possible link between PAHs exposure and the prevalence of reproductive tract infections in women. Further studies are needed to confirm these associations.